The effect of progressive muscle relaxation education on the quality of sleep in elderly people with hypertension at the South Cilacap Community Health Center - Priyanto, Budi; Atmojo, Bayu Seto Rindi (Indonesian Nursing Journal, 2024)
Background: The elderly experience a decreased sleep phase as a result of poor sleep, meaning that they tend to be restless and easily awakened, which can interfere with sleep quality. It can result in physical tension, which affects the increase in blood pressure. Progressive muscle relaxation therapy can improve sleep quality and control tension and anxiety by training patients to consciously relax their body muscles. Purpose: To analyze the effect of progressive muscle relaxation education on the quality of sleep in elderly people with hypertension at the South Cilacap Community Health Center. Methods: This research was conducted on elderly people with hypertension at the South Cilacap Community Health Center  using a quasi-experimental research design with a non-equivalent control group design. Simple random sampling was used with a total of 46 respondents. The data were analyzed using a T-test. Results: The results of the study found an increase in the average score on the sleep quality scale, and after progressive muscle relaxation education, the intervention group found a mean pre-test score of 15.57 and in the post-test section a mean score of 5.57. In the control group, the pre-test had a mean value of 14.52, and in the post-test section, the mean value was 12.70. and the results of further analysis of the independent t-test between the intervention group and the control group showed p = 0.000. Conclusion: There was an effect of progressive muscle relaxation therapy on the sleep quality of elderly people in the intervention group among elderly people with hypertension at the South Cilacap Community Health Center. There was a significant difference in the average PSQI score in the post-test measurements of both the intervention and control groups. Progressive muscle relaxation is an alternative therapy designed to reduce muscle tension, which can then relax muscles ranging from facial muscles to leg muscles